Efficient method for DCT-domain image arbitrary downsampling - DU Yao-gang1; CAI An-ni2 (Tongxin xuebao)
A novel approach to resize Images with m/n resizing ratio in the DCT domain,was proposed which expoits the relationship of DCT coefficients between m 2input blocks and n 2output blocks.Experimental results confirm that the scheme performs about 0.5dB better than Park’s method in terms of PNSR of reconstructed image with a comparable computational speed.The proposed method can be used to any DCT-based compressed video transcoding applications.